Character Building or The Development of the Personality: An Innovative Methodological Platform in the Informational Educational Space - Berulava, Mikhail Nikolaevich; Berulava, Galina Alekseevna (International Dialogues on Education Journal, 2018)
Currently an acute crisis exists regarding the traditional methodological platform of the higher education system. Research continues with studies of individual facets of human personality without referring to new methodological realities. The dominant model of the University has remained unchanged for about 200 years. Today, however, the goals, means and agents of socialization are changing. In this essay, a new methodological platform for personality development is proposed and discussed, one which examines the role of behavioral stereotypes in the social and professional success of the individual.